Addressing the Challenge of Overlapping Claims in Implementing the Vancouver Island (Douglas) Treaties - Thom, Brian (Anthropologica, 2020)
<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Indigenous social and legal orders are a source for addressing the challenge of overlapping claims in exercising historic treaty rights in the territories of neighbouring non-treaty Indigenous Peoples. The Vancouver Island Treaties (also known as the Douglas Treaties) of the 1850s made commitments that signatory communities could continue to <em style="box-sizing: border-box; color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">hunt on unoccupied lands and carry on their fisheries as formerly<span style="color: #000000; font-family: ’Open Sans’, Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">. Today, as urban, agricultural and industrial forestry have constrained where people can exercise their treaty rights locally, individuals from these nations exercise harvesting rights in “extended territories” of their neighbours. Through detailing several court cases where these treaty rights were challenged by the Crown and the texts of modern-day treaty documents, I show how Coast Salish people continue to draw on local values and legal principles to articulate their distinctive vision of territory and community, both engaging and subverting divisive “overlapping claims” discourses. Not only First Nations but the state, through the judiciary, Crown counsel and land claims negotiators, also, at times, acknowledge and recognise the principles of kin and land tenure that are the foundation for addressing the challenges of overlapping claims.